2017
DOI: 10.1016/j.csr.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Inner-shelf ocean dynamics and seafloor morphologic changes during Hurricane Sandy

Abstract: A B S T R A C THurricane Sandy was one of the most destructive hurricanes in US history, making landfall on the New Jersey coast on October 30, 2012. Storm impacts included several barrier island breaches, massive coastal erosion, and flooding. While changes to the subaerial landscape are relatively easily observed, storm-induced changes to the adjacent shoreface and inner continental shelf are more difficult to evaluate. These regions provide a framework for the coastal zone, are important for navigation, agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Simulated subtidal fluctuations lagged behind the observations due in part to the large‐scale model forcing in this area during Hurricane Sandy [ Warner et al ., ]. The main source of uncertainty in simulating storm conditions such as Hurricane Sandy is the available wind forcing.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated subtidal fluctuations lagged behind the observations due in part to the large‐scale model forcing in this area during Hurricane Sandy [ Warner et al ., ]. The main source of uncertainty in simulating storm conditions such as Hurricane Sandy is the available wind forcing.…”
Section: Discussionmentioning
confidence: 99%
“…Because this process is robust across these two extreme cases drawn from the 30 year envelope of MAB summer cyclones, it will be critical to resolve and forecast the same process for future storms, with the goal of lowering the uncertainty in predictions of TC impacts. Realistic 3‐D coupled models that assimilate coastal observatory data and that are capable of predicting the ahead‐of‐eye‐center stratified coastal ocean cooling processes will be critical [e.g., Zambon et al ., ; Warner et al ., ]. The increasingly populated [ Peduzzi et al ., ] at‐risk coastlines—the Northeast U.S. and northeastern China and Korea—adjacent to the two most stratified seas in the world—the MAB and Yellow Sea—will be increasingly vulnerable to TCs as sea levels rise [ Hansen et al ., ], as TCs more frequently and severely undergo rapid intensification just before landfall [ Emanuel , ], and if maximum TC intensities continue to migrate poleward [ Kossin et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the differences between the deep, open ocean processes and the coastal processes are stark due to the influence of the bottom boundary layer and coastal wall in shallow water [ Glenn et al ., ; Seroka et al ., ]. It is critical to close this gap, with the goal of improving the simulation of coastal ocean physics in coupled TC intensity models [e.g., Zambon et al ., ; Warner et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the extensive studies on the ocean response and feedback in the open oceans, some studies have also paid attention to the response of the shallow ocean water in coastal regions, where the thermodynamic and dynamic features often change significantly due to the development of the bottom boundary layer and the wind-driven coastal circulation during the forced period (e.g., Liu et al, 2011;Warner et al, 2017). Among these studies, Mahapatra et al (2007) suggested that the left-shifted cold wake after TC Orissa (1999) was due to the impedance of the coastline to the circulation in the Bay of Bengal.…”
Section: Introductionmentioning
confidence: 99%